Modelling livestock test-and-treat: A novel One Health strategy to control schistosomiasis and mitigate drug resistance - Díaz, Adriana V.; Lambert, Sebastien; Neves, M. Inês; Borlase, Anna; Léger, Elsa; Diouf, Nicolas D.; Sène, Mariama; Webster, Joanne P.; Walker, Martin (Frontiers in Tropical Diseases, 2022)
Schistosomiasis, a neglected tropical disease, is a widespread chronic helminthiasis reported in 78 countries, predominantly those within sub-Saharan Africa, as well as Latin America, Asia, and most recently, even Europe. Species of the causative blood fluke infect not only humans but also animals, and hybrids between previously assumed human-specific and animal-specific schistosomes are being increasingly reported. Existing control programs across Africa focus on humans and rely heavily on mass drug administration of praziquantel, the sole drug available against schistosomiasis. Praziquantel is safe and highly efficacious but could become ineffective if resistance emerges. To reach the revised World Health Organization goal of elimination of schistosomiasis as a public health problem, and interruption of transmission within selected regions by 2030, new consideration of the role of animal reservoirs in human transmission in general, and whether to also treat livestock with praziquantel in particular, has been raised. However, whilst there are no dedicated control programmes targeting animals outside of Asia, there are emerging reports of the use and misuse of praziquantel in livestock across Africa. Therefore, to effectively treat livestock in Africa and to help mitigate against the potential evolution of praziquantel resistance, structured control strategies are required. Here, using a transmission modelling approach, we evaluate the potential effectiveness of a theoretical test-and-treat (TnT) strategy to control bovine schistosomiasis using a currently available point-of-care diagnostic test (developed for human use) to detect circulating cathodic antigen (POC-CCA). We show that implementing TnT at herd-level from 2022 to 2030 could be highly effective in suppressing infection in cattle and even, in lower prevalence settings, reaching nominal ‘elimination’ targets. We highlight the importance of enhancing the specificity of POC-CCA for use in livestock to avoid unnecessary treatments and discuss the outstanding challenges associated with implementing TnT as part of a holistic One Health approach to tackling human and animal schistosomiasis.